Tanggung Jawab Profesi Advokat Dalam Pendampingan Hukum Perkara Pidana terhadap Klien - Rizki Ananda Utami(; Sari Ramadani(; Fauziah Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Advocate is a law enforcement and a free, independent and responsible job in enforcing the law guaranteed by law. It means that lawyers have rights, obligations and responsibilities in accordance with the rules of law advocate. On going professional duties, advocates are expected to act professionally and don’t discriminate in providing advice legal to the clients. Through the legal services provided, advocate stints the profession for justice under the law for the benefit of justice seekers, including efforts to empower communities to realize their fundamental rights before the law. Keywords: Responsibility, Advocate, Legal Assistance